Perlindungan Hukum Terhadap Konsumen Atas Alat Kesehatan (Masker) Yang Dilakukan Pelaku Usaha Pada Aplikasi Bukalapak - Amdery, Grace Nathalia; Akyuwen, Rory Jeff; Pariela, Marselo Valentino Geovani (Faculty of Law, Universitas Pattimura, 2022)
Introduction: The protection of consumer rights and obligations is often neglected because of the attitude of business actors who want to get profit by taking advantage of certain situations and conditions, one of which is where the consumer's need for medical devices in the form of masks is hindered by selling costs that are too high from the market price. Purposes of the Research: The purpose of this study is to answer how the legal protection for consumers for default by business actors on the Bukalapak application is.Methods of the Research: This study uses a normative juridical method by using a statutory and conceptual approach.Results of the Research: The results of this study indicate that in the online sale and purchase agreement, business actors have defaulted on Bukalapak and have resulted in losses to consumers, referring to Article 1243 of the Civil Code which explains about compensation and also Article 19 of the Consumer Protection Act. related to consumer rights to demand compensation. Reimbursement of loss costs must be carried out by Bukalapak for actions taken by business actors in terms of increasing prices unilaterally and Bukalapak must be responsible for the losses incurred.